Predicting vulnerability to stress based on psychological capitals and personality traits in the treatment staff of Corona - Yousefi, Mehnoosh; Fattah Andabil, Azam; Mashayekh, Maryam (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2021)
Background and purpose: Considering the importance of maintaining the medical force and keeping this group healthy as people who protect the health and well-being of other members of society, it is necessary to investigate the level of their anxiety and psychological pressure as well as the relative factors so that based on the results, steps can be taken to maintain and improve their mental health. Therefore, the present study aimed to predict vulnerability to stress based on psychological capital and personality traits in the treatment staff of Corona. Methodology: The research method was a correlation-descriptive type. The statistical population of the present study included all the treatment staff of the hospitals dealing with Corona in Tehran in 2020, and 228 people were selected as a statistical sample using the convenience sampling method. The data collection tool included the short-form Neo McCree and Costa (1985) personality questionnaire, the Luthans et al. (2007) psychological capital questionnaire, and the Seyed Khorasani and Sediqani (2008) stress syndrome measurement scale. Results: Pearson’s correlation coefficient and regression analysis showed that personality traits and psychological capital have a correlation coefficient of 0.62 with the vulnerability to the stress of corona treatment staff. This means that 39% of the total variance of the stress vulnerability of the Corona treatment staff is explained by personality traits and psychological capital (P<0.05). Conclusion: The results showed that among the personality traits, neuroticism, openness to experience, agreeableness, and conscientiousness, and among the psychological capitals, self-efficacy and optimism could predict the vulnerability to stress of the corona treatment staff.